Identifying users' requirements to assist in the delivery of portable lifetime health records via health cards / Muhammad Arif M. Hashim - M. Hashim, Muhammad Arif (2002)
The current health system in Malaysia is fragmented and there is yet a binding factor that effectively integrate both the public and the private healthcare services. Health records of one's lifetime or known as Lifetime Health Record (LHR) is identified to assist this. It can be shared to facilitate consultation and review past medical problems and treatment and to aid in future clinical intervention. For LHR to be beneficial, it has to be portable and can be carried around when there is a need. One of the ways is to incorporate LHR into the health card.